Pengembangan Biodiesel Kelapa Sawit Indonesia dalam Mencapai Target Bauran Energi Baru Terbarukan Tahun 2025 - Salsabila, Nisa; Ernah, Ernah; Trimo, Lucyana; Suminartika, Eti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Indonesia is experiencing a deficit in crude oil, necessitating the country to import oil from other nations. In response to this, the government has issued policies to replace fossil fuels with biodiesel, especially from palm oil. Palm oil biodiesel is identified as a crucial component in achieving the renewable energy blend targets set by the government. This research employs a descriptive qualitative method with a case study approach to analyze the factors influencing the development of palm oil biodiesel. The results of the analysis of internal and external factors indicate that palm oil biodiesel has the strength to enhance the value-added of palm oil products. However, there are weaknesses related to uneven fuel supply storage. The most significant opportunities lie in a promising market due to the consistently high demand for fuel, but threats arise from palm oil production prioritized for export. Through a SWOT analysis, six strategies are derived to ensure the sustainability of biodiesel production, enhance the quality of operational facilities, and provide transparent information to the public. Subsequently, the SMART Goals analysis sets specific, measurable, achievable, realistic, and timely targets for the new renewable energy blend through the specific development of palm oil biodiesel. This research focuses on concrete strategies and steps that can be implemented to optimize the role of palm oil biodiesel in achieving new renewable energy targets in Indonesia.